2018
DOI: 10.1111/jog.13581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyaluronic acid–enriched transfer medium on frozen–thawed embryo transfer outcomes

Abstract: HETM can improve the embryo IR and clinical PR in patients with repeated implantation failure in the third or more FET attempt. However, the use of HETM for first and second FET should be done with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Our results are in agreement with those of previous studies ( 30 ), which showed that the addition of HA to the transfer medium in patients with RIF significantly increased the implantation and clinical pregnancy rates while not affecting the ectopic pregnancy and abortion rates. The mechanism of this beneficial effect might be that the addition of HA to the transfer medium increases its viscosity, which may enhance the embryo transfer process and reduce the possibility of the expulsion of embryos from the uterine cavity after transfer.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with those of previous studies ( 30 ), which showed that the addition of HA to the transfer medium in patients with RIF significantly increased the implantation and clinical pregnancy rates while not affecting the ectopic pregnancy and abortion rates. The mechanism of this beneficial effect might be that the addition of HA to the transfer medium increases its viscosity, which may enhance the embryo transfer process and reduce the possibility of the expulsion of embryos from the uterine cavity after transfer.…”
Section: Discussionsupporting
confidence: 93%
“…HA-enriched media may increase the implantation rate 14 and clinical pregnancies in patients with previous failed implants and in the third or more attempts after cryo ET. 10,15 They also report that clinical pregnancies and implantation rates were higher in embryos after cryo ET, indicating that the viscosity of the EG medium physically protects embryos after assisted hatching. 13 Zhang et al 16 and Wu et al 17 investigated whether EG has an impact on pregnancy outcome during in vitro fertilisation compared to G2 medium.…”
Section: Discussionmentioning
confidence: 97%
“…First-time FET patients or those with one previous FET have no significant clinical benefit with the use of HETM, whereas patients on their third or higher FET attempt resulted in a statistically significant increase in implantation (33.3 vs. 16.4%) and pregnancy rate (52.2 vs. 27.4%) when compared with standard media (p < 0.001, n ¼ 1,632). 20 Conversely, the use of EmbryoGlue in donor FET cycles following preimplantation genetic testing (PGT) did not show any significant improvement in clinical pregnancy rates or any significant decrease in rates of miscarriage (p ¼ 0.32), although it should be noted that this was a small case-control study (n ¼ 37) which may limit the significance of the results. 21 The short protocol for EmbryoGlue provided by Vitrolife states that embryos can be held in EmbryoGlue for a minimum of 10 minutes and a maximum of 4 hours prior to transfer.…”
Section: Recent Evidencementioning
confidence: 89%